Empowerment of Small and Medium Enterprises (SMEs) Through Social Networks in Coastal Area of Surabaya City - wildan taufik raharja (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2021)
This research aims to examine social networks that can be accessed by SMEs. Capital has an important role in empowering SMEs in the Coastal Areas of Surabaya City. Some previous studies have shown that empowerment of SMEs is only seen from an economic perspective, such as product marketing, product design, and the role of SMEs in local economic growth. In this study it looks for social networks (stakeholders) with an important role in empowering SMEs and can be accessed by SMEs. This study uses a qualitative method with a case study research strategy. The method of finding data uses in-depth interviews, observation, and documentation. Â There are 7 informants from SMEs owners, SMEs associations, government, and private institutions. Data analysis begins with data collection, data reduction, data presentation, and making conclusions / verification. The results of this study showed 5 social network stakeholders that can be accessed by SMEs, namely SMEs, SMEs Associations, Government, Banks, and Private. Â The government is the most important institution in developing SMEs. While the limitation of this research is that it has not been able to see further the role of stakeholders that can be accessed by SMEs. Further research can examine the role of stakeholders in SMEs empowerment social networks